Using Communicative Games to Improve Students’ Speaking Skill at SMPN 2 LAMASI - AD, Fibri Indira Lisanty; DM, Jumriani (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2021)
This research aims to determine the effectiveness of communicative games that can improve students’ speaking skills in class VIII at SMPN 2 Lamasi. The method that is applied in this research is a pre-experimental design. The population in this research is the seventh-grade students of SMPN 2 Lamasi, and the total sample is 15 students. The research uses a cluster random sampling technique in determining the sample. The instrument of this research is speaking. The results of this research indicated that after using the communicative games to improve students' speaking skills of SMPN 2 La masi increases. This shows that there are significant differences between student scores in pre-tests and post-test. The mean score of the students’ pre-test is 37.47 and 81.47 in the post-test. So, there is significant different between the result of pre-test and post-test after the treatment. Therefore, the researcher concludes that communicative games is effective in teaching speaking at eight grade of SMPN 2 Lamasi.